Confined turbidite sand-sheets in the Paraná and Paganzo Basins - Carvalho, Bruno Miguel Vaz de (2014)
During the Late Paleozoic, Gondwana was home for a protracted glaciation that generated high sediment supplies and ample accommodation space within incised valleys and fjords, usually laterally confined and longitudinally extensive geomorphological features. These glacial valleys became so overdeepened below sea level that they filled up with hundreds of meters of seawater, as glacio-eustatic sea level rose during and following deglaciation, therefore producing deep-water environments prone to gravity-flows such as turbidity currents. This study assesses the behavior and morphology of sand sheets deposited by turbidity currents that instead of flowing outward onto an unconfined basin floor, were confined within a limited space up to a spill point. This study compare three examples of turbidite sand sheet deposited on settings presenting distinct degree of confinement, including two areas in the Paganzo Basin (Paganzo Group) and one area in in the roughly coeval Paraná Basin (Itararé Group) The Argentinean case studies are located in the eastern Precordillera of the Andes, near San Juan city, and include a palaeofjord (Quebrada de Las Lajas) and a more open valley (Quebrada Grande), both incised into Early Paleozoic shelf carbonates (San Juan Formation) and olistostrome (Rinconada Formation). The Brazilian counterpart is located in Vidal Ramos (Santa Catarina State, Southern Brazil) and it is a very wide palaeovalley carved into Proterozoic schists and secondly marbles. After a general description and interpretation of the valleys fills and a more detailed description and interpretationof the associated turbidite sand sheets, their similarities and differences are stressed to define which features ewere dependent or independent of the glacial valley morphology.